Dynamic capabilities: Antecedents and implications for firms' performance - Correia, R. J.; Teixeira, M. S.; Dias, J. G. (International Journal of Productivity and Performance Management, 2022)
Purpose: This paper aims to explore a new causal link between learning, market and entrepreneurial orientations and firms' performance by introducing dynamic capabilities and competitive advantages as mediator variables. Design/methodology/approach: The mediating role of dynamic capabilities and competitive advantages is tested using a sample of 1,190 Portuguese firms, and structural equation models. Findings: It is shown that dynamic capabilities mediate the relationship between the three orientations–learning, market and entrepreneurial–and competitive advantages of differentiation and cost leadership, and both competitive advantages lead to firm's performance. It is also shown that learning orientation is an antecedent of market orientation and entrepreneurial orientation. Practical implications: This research shows that firm's performance depends on the capacity of firms to learn, innovate, be proactive, take risks and collect the best market data. Indeed, by optimizing the internal management and knowledge dissemination, firms will develop a set of capabilities and competitive advantages that lead to an appropriate response to market challenges. Originality/value: This study tests the relationship between strategic orientations and firm's performance by taking the mediating effects of dynamic capabilities and competitive advantages into account. This research was conducted in Portugal.